Discuss on the Exploration and Practice of Information Communication Network Fault in the Centralized Monitoring Mode - Yang Wang (Dianxin kexue)
With the development of the information communication network equipment functions and business services, intensive management of the information communication network is gradually turning into a new management model. The influencing factors of management span planning were discussed based on flatting centralized monitoring and hierarchical fault management. The functional mechanism, announcements, strategies and methods were discussed from the six fault management aspects（equipment alarm obtaining, alarm standardized management, alarm rules and analysis, fault work order pretreatment, channel optimization and contingency plan， process through and quality control）. The engineering practical value and management supporting values of emerging technology were analyzed in centralized fault management,such as big data technology,virtualization technology,etc.